Masjid Jogokariyan: Pemberdayaan Ekonomi dan Penguatan Pendidikan Umat di Yogyakarta - Ni'mawati, Ni'mawati; Wibowo, Marsudi Fitro; Ihwanudin, Nandang; Azmi, Amaliah Al (FASTABIQ: JURNAL STUDI ISLAM, 2024)
This study examines the philosophy of economic empowerment in the Islamic education sector at the Jogokariyan Mosque in Yogyakarta. The Jogokariyan Mosque has successfully utilized Zakat, Infak, Charity, and Waqf (ZISWAF) funds productively to support economic and educational empowerment programs. The purpose of this study is to analyze the philosophy of economic empowerment at the Jogokariyan Mosque, educational financing at the Jogokariyan Mosque, and the results of economic empowerment in the education sector towards improving the spiritual and welfare of beneficiaries. This study uses a case study method, with data collection techniques through interviews, observations, and documentation. The results of the study show that the Jogokariyan Mosque not only functions as a place of worship, but also as a center for economic and social activities. The mosque management implements various empowerment programs that include providing business capital, educational assistance, and other social programs aimed at improving the quality of life of the community. The philosophy underlying economic empowerment at the Jogokariyan Mosque is to restore the function of the mosque as it was during the time of the Prophet Muhammad SAW, as the center of community activities. With this vision, the mosque is able to create a more economically independent and highly competitive society. This study provides insight and inspiration for other institutions to develop similar programs that can strengthen the economic and spiritual independence of the community. The implementation of the empowerment program at the Jogokariyan Mosque proves that with professional management, the mosque can become a center of civilization that advances MuslimsKeywords: Economic Empowerment; Islamic Education; Mosque